2014
DOI: 10.1093/mnras/stu641
|View full text |Cite
|
Sign up to set email alerts
|

Detection of vibronic bands of C3 in a translucent cloud towards HD 169454

Abstract: We report the detection of eight vibronic bands of C 3 , seven of which have been hitherto unobserved in astrophysical objects, in the translucent cloud towards HD 169454. Four of these bands are also found towards two additional objects: HD 73882 and HD 154368. Very high signal-to-noise ratio (∼1000 and higher) and high resolving power (R = 80, 000) UVES-VLT spectra (Paranal, Chile) allow for detecting novel spectral features of C 3 , even revealing weak perturbed features in the strongest bands. The work pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 59 publications
5
17
0
Order By: Relevance
“…12 Furthermore, with the identification of its cation, C 60 + , as the carrier of initially two and later four diffuse interstellar bands (DIBs) in the nearinfrared of the diffuse interstellar medium (ISM), [13][14][15] research into this molecule is forcing us to reevaluate our understanding of interstellar molecular complexity. For a long time C 3 was the largest pure carbon species identified in diffuse clouds 16,17 and thus, the detection of C 60 + substantially stretches the size-limit for carbon-containing molecules in the diffuse ISM which could hold the key to unravelling the rest of the DIB mystery which has remained unsolved for almost a century at the time of writing. [18][19][20][21] The question of how C 60 forms in interstellar space has given rise to some convincing hypotheses, 22 especially in light of the apparent inverse relationship between the abundance of polycyclic aromatic hydrocarbons (PAHs) and C 60 at decreasing distances towards stars.…”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, with the identification of its cation, C 60 + , as the carrier of initially two and later four diffuse interstellar bands (DIBs) in the nearinfrared of the diffuse interstellar medium (ISM), [13][14][15] research into this molecule is forcing us to reevaluate our understanding of interstellar molecular complexity. For a long time C 3 was the largest pure carbon species identified in diffuse clouds 16,17 and thus, the detection of C 60 + substantially stretches the size-limit for carbon-containing molecules in the diffuse ISM which could hold the key to unravelling the rest of the DIB mystery which has remained unsolved for almost a century at the time of writing. [18][19][20][21] The question of how C 60 forms in interstellar space has given rise to some convincing hypotheses, 22 especially in light of the apparent inverse relationship between the abundance of polycyclic aromatic hydrocarbons (PAHs) and C 60 at decreasing distances towards stars.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the DIB carriers and measuring their response to physical conditions and chemical compositions of interstellar clouds is of high importance. This would add to our rather limited knowledge of the molecular inventory of these clouds in which small molecules, like C3 (Schmidt et al 2014) were long the largest species identified. It also would be key to understanding the life cycle of cosmic dust and carbonaceous compounds from dying star ejected envelopes to the birth places of new stars and planetary systems.…”
Section: Introductionmentioning
confidence: 99%
“…This is an exciting result because C 60 (Cami et al 2010; Sellgren et al 2010), and C60+ (Berné et al 2013) have also recently been detected in space through their mid-infrared emission spectra. This identification may be a chemical clue towards identifying further DIB carriers; so far only C 3 (Haffner & Meyer 1995; Maier et al 2001; Schmidt et al 2014) and C60+ have been identified as pure polyatomic carbon species in the diffuse ISM and this leaves a large gap to be filled in our current understanding of the carbon chemical network in diffuse clouds. It is possible that the detection of C60+ hints at a long predicted important role of polycyclic aromatic hydrocarbons (PAHs) in the ISM (Van der Zwet & Allamandola 1985; Léger & d’Hendecourt 1985; Salama et al 1996).…”
Section: Introductionmentioning
confidence: 99%